IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM PENINGKATAN MUTU PENDIDIKAN PADA MTsN GRONG-GRONG KABUPATEN PIDIE - Muhammad Judin; Cut Zahri Harun; Sakdiah Ibrahim (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
The objective of this research was to determine the planning, implementation, and evaluation in improving the quality of education. This study used a qualitative approach with descriptive method. The technique of collecting data through interviews, observation and documentation. Subjects in this study is the principal, vice principal, teachers, and chairman committee of MTsN Grong Grong Pidie district. The results of this study indicate that: (1) planning program based on the vision, mission, and goals of the school. The work program drawn up by each component of the school by revising the annual work program and verified by the school principal. Substance leads to improving the quality of education but does not specify the target results in detail. (2) The implementation of each component of the program is managed by the school, by setting up implementation guidelines such as documents written educational unit level curriculum, organizational structure, job descriptions of teachers and education personnel, academic regulations, and school rules.. (3) Evaluation of the program is more focused on the academic program of the effectiveness and efficiency of learning and teacher performance, carry out self evaluation of schools and school accreditation. The results of the evaluation made a report consisting of technical and financial reports to The Head Office of District Religious Ministry.Keywords: School Based Management and Quality of Education